Impact of ocean acidification on the physiology of digestive gland of razor clams Sinonovacula constricta - Liang, Jian; Liu, Yuhang; Zhu, Feixia; Li, Yongren; Liang, Shuang; Guo, Yongjun (Frontiers in Marine Science, 2022)
Ocean acidification (OA) can have widespread implications for marine bivalves. While our current understanding of OA effects on the physiological performance is increasing, very little is known about the physiology of digestive gland of marine bivalves in response to OA. Here, we examined how the digestive system of razor clams (Sinonovacula constricta) responded to OA. Following 35-day exposure to CO2-driven seawater acidification, no significant decreases in phenotypic traits, such as dry body weight gain, specific growth rate, condition index and survival rate, as well physiological functions, such as activities of antioxidant and digestive enzymes, were observed, demonstrating the resistance of razor clams under acidified conditions. Histological results showed that some direct damages on the structure of digestive gland was observed, including degradation of digestive tubular, atrophy of epithelial cells, loose cell arrangement, even diffuse. This study provides insights into the digestive performance of marine bivalves in a rapidly acidifying ocean.